Distribution and genetic diversity of microbial populations in the pilot-scale biofilter for simultaneous removal of ammonia, iron and manganese from real groundwater. (September 2017) - Cheng, Qingfeng; Nengzi, Lichao; Bao, Linlin; Huang, Yang; Liu, Shengyu; Cheng, Xiuwen; Li, Bo; Zhang, Jie
Abstract: A pilot-scale biofilter treating real groundwater was developed in this study, which showed that ammonia, iron and manganese were mainly removed at 0.4, 0.4 and 0.8 m of the filter bed, respectively, and the corresponding removal efficiencies were 90.82%, 95.48% and 95.90% in steady phase, respectively. The variation of microbial populations in the biofilter during start-up process was also investigated using high-throughput pyrosequencing (HTP). Results indicated that the main functional microbes for ammonia, iron and manganese removal were Nitrosomonas, Crenothrix and Crenothrix, respectively, which was mainly distributed at 0.8, 0, and 0.8 m of the filter bed with a corresponding abundance of 8.7%, 28.12% and 11.33% in steady phase, respectively. Kinds of other bacteria which may be related to methane, hydrogen sulfide and organic matter removal, were also found. In addition, small part of archaea was also detected, such as Candidatus Nitrososphaera, which plays a role in nitritation. Graphical abstract: Highlights: Simultaneous removal of NH4 +, Fe 2+ and Mn 2+ was achieved from real groundwater. AOB, NOB, AOA, IOB, IOA, MnOB were coexisted in the biofilter. Microbial populations varied along the biofilter depth. Microbial populations varied during the start-up process. Bacteria distribution could be the main factor to affect biofilter performance.